Pelatihan Resiliensi Untuk Menurunkan Perceived Stress Selama Masa Pandemi Covid-19 - Marina Pristiarawati; Alvina Prameswari; Hartanti Hartanti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The COVID-19 pandemic that its first case in Indonesia found in March 2020 urged society to adapt to a new lifestyle. Offline meetings were restricted to avoid the transmission of COVID-19, therefore, online meetings have become a new lifestyle presently. This process of adapting to online’s lifestyle happens universally in such workplaces and educational institutions of kindergartens to colleges. This sudden adaptation makes society experience some pressure which also affects an individual’s stress and wellbeing. Teachers at one of the special needs schools in Sidoarjo, Indonesia, experience stress due to the pressures they had while adapting to online teachings. Resilience training is given as an intervention to help teachers decrease their level of stress. The training is scheduled for 3 (three) days and holds 6 (six) sessions via Zoom Meeting. The data result is analyzed using Wilcoxon differentiate test for resilience and perceived stress scores before and after the training. The result shows a difference between resilience and perceived stress scores before and after the training session with a significance score of 0,005 (p<0,05). This result concludes that resilience training can decrease the level of perceived stress that the teachers experienced.